2005
DOI: 10.1007/s00402-004-0772-4
|View full text |Cite
|
Sign up to set email alerts
|

Five-year results of two cemented hip stem models each made of two different alloys

Abstract: Stem design and even more alloy may influence the survival rate and clinical outcome. Evaluating the results, we recommend the use of the classic straight stem prosthesis made of cobalt chromium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The 20-year survival of the original MSS (Co) exceeds 86% with aseptic loosening as the endpoint, and is comparable to that of other successful cemented implants (Clauss et al 2009). However, later developments in the stem design have been proven to reduce short- and mid-term survival instead of bringing about further improvements as expected (Maurer et al 2001, Schweizer et al 2005). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 20-year survival of the original MSS (Co) exceeds 86% with aseptic loosening as the endpoint, and is comparable to that of other successful cemented implants (Clauss et al 2009). However, later developments in the stem design have been proven to reduce short- and mid-term survival instead of bringing about further improvements as expected (Maurer et al 2001, Schweizer et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…The patients had a clinical and radiographic follow-up after 1, 2, 5, 10, and 15 years. After 5 years of follow-up, survival analysis showed inferior results for Ti stems with the SL design compared to the Co stems with the MSS design (Schweizer et al 2005). Analyzing the Ti stems after 10 years, Maurer et al (2001) found male sex, age of < 65 years, a small stem, and the SL design to be risk factors for aseptic loosening.…”
Section: Methodsmentioning
confidence: 99%
“…The differences are huge between metals (CoCrMo and stainless steel) and cement or cortical bone, which is likely to cause debonding and subsidence. However, subsidence of titanium alloy stem is only 0.14-2 mm, and the incidence of survival of titanium alloy stem is higher than that of CoCrMo and stainless steel (Akiyama et al, 2011;Schweizer et al, 2005). Similarly, additional clinical and radiological studies of other cemented titanium stems have also shown good survival results, with Ultima straight collarless titanium stems having 97% survival after 7.5 years, BiCONTACT and Müller straight titanium stems 97% survival after 11 years, and Müller straight collarless titanium stems coated with titanium oxide 96.8% survival after 9 years (Bowditch, 2001;Eingartner et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have shown that titanium stems reduce loosening and proximal bone loss when compared with cobalt-chrome stems, whereas others show higher rates of early clinical failure. 14,16,[22][23][24] One concern about titanium femoral stems is that their increased flexibility can increase cement stresses, resulting in failure. 14,15,22 Another concern is that titanium femoral stems have been susceptible to corrosion.…”
Section: Discussionmentioning
confidence: 99%